2007
DOI: 10.1063/1.2777121
|View full text |Cite
|
Sign up to set email alerts
|

Polarization characteristics of photonic quantum ring laser with three-dimensional whispering gallery resonances

Abstract: We report polarization characteristics of light from a photonic quantum ring ͑PQR͒ laser of three-dimensional ͑3D͒ whispering gallery modes. The 3D polarization states of light from the PQR laser were studied with a home-built solid-angle scanner capable of detecting the spatial intensity distribution in a wide range of solid angles. The analysis shows that the dominant polarization vectors of the PQR laser emitting in the surface normal direction lie always tangential to the PQR perimeter, which means there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…As said before, the resonance of the PQR laser results in 3D WCM of helical standing waves, which is surface-normal dominant, in contrast to the in-plane 2D WG mode. The data taken with a home-built solid angle scanner setup, which will be discribed later, shows a tangential polarization dominance which supports strong carrier-photon couplings behaviors needed for the PQR formation (Kim et al, 2007) …”
Section: Spatio-temporal Dynamic Simulation Of Pqr Standing Waves Andmentioning
confidence: 65%
“…As said before, the resonance of the PQR laser results in 3D WCM of helical standing waves, which is surface-normal dominant, in contrast to the in-plane 2D WG mode. The data taken with a home-built solid angle scanner setup, which will be discribed later, shows a tangential polarization dominance which supports strong carrier-photon couplings behaviors needed for the PQR formation (Kim et al, 2007) …”
Section: Spatio-temporal Dynamic Simulation Of Pqr Standing Waves Andmentioning
confidence: 65%
“…We then pay attention to this region where one expects to observe this resultant optical pattern of quasi-2D standing waves in the QW W Rayleigh region. The dominant azimuthal-axis polarization (Kim et al 2007) will then give rise to a 2D strong carrier coupling responsible for the PQCE, transiently inducing the concentric PQRs for imminently recombinant carriers (Kwon et al 2006). This is the most probable reason for the observation of very low quantum-wire-like threshold currents.…”
Section: Properties Of Wcm Laser Of Pqrmentioning
confidence: 95%
“…While the transverse and lateral profiles of the helix modes of the WCM are worth further advanced studies, we have earlier reported a simpler ray-optic model of effective 3D WCM helixes by combining the radial-azimuthal TIR wave in the r -φ plane with the vertically confined (y-axis) wave component between top and bottom DBR mirrors (Bae et al 2003). The two counter propagating 'curved' helixes of clockwise (CW) and counterclockwise (CCW) waves in the 3D WCM actually share the same helical path back and forth, and their vectorial sum gives rise to the output propagating in radial direction (Park et al 2002), with azimuthalaxis polarization (Kim et al 2007). In the course of lasing the 3D helical standing waves transiently induces concentric PQRs ( Fig.…”
Section: Properties Of Wcm Laser Of Pqrmentioning
confidence: 99%
“…Moreover, we have observed unusual convex WCMs from reverse-mesa (¼hole)-type micro-resonators, whose WCMs we interpreted with respect to gain-guiding and photonic quantum corral effects [2,4]. Based on the concave and convex WCM properties of the PQR, we have further demonstrated a new type of optical encoder operating through s-and p-polarisation switchings of a zigzag-shaped PQR laser [5], the 3D polarisation states of light from which were analysed in [6]. Although the PQR laser has the advantages mentioned above, it still needs to deliver output power sufficiently large to compete with high-power LEDs.…”
mentioning
confidence: 99%